2003
DOI: 10.1017/s1041610203008846
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Disease Ethics—Informed Consent and Related Issues in Clinical Trials: Results of a Survey Among the Members of the Research Ethics Committees in Sweden

Abstract: The rapid advances in biomedical sciences have induced special moral and ethical attitudes, which ought to be taken into account. One of the most essential issues is the principles for participation in research of subjects with reduced decision-making capacity.We conducted a questionnaire survey among members of the research ethics committees in Sweden to find out their attitudes to a range of ethical issues related to research on subjects with Alzheimer's disease. One hundred thirty-six of those approached re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
6
0
10
Order By: Relevance
“…Although they elicited opinions differently by presenting hypothetical or actual studies, these studies also concluded that a large number of older adults (Wendler et al ., 2002; Ayalon, 2009; Karlawish et al ., 2009; Kim et al ., 2009a) and informal caregivers of persons with dementia (Karlawish et al ., 2008; Kim et al ., 2010) support proxy consent from a family member. Research Ethics Committee members are largely in favor of proxy consent to research from a family member if there is “potential therapeutic benefit for the subject and no more than minimal risk for adverse events” (Peterson and Wallin, 2003). The proportion in favor of proxy consent however drops substantially if there is “no potential therapeutic benefit for the subject with no more than minimal risk for adverse events but potential therapeutic benefit to others”.…”
Section: Discussionmentioning
confidence: 99%
“…Although they elicited opinions differently by presenting hypothetical or actual studies, these studies also concluded that a large number of older adults (Wendler et al ., 2002; Ayalon, 2009; Karlawish et al ., 2009; Kim et al ., 2009a) and informal caregivers of persons with dementia (Karlawish et al ., 2008; Kim et al ., 2010) support proxy consent from a family member. Research Ethics Committee members are largely in favor of proxy consent to research from a family member if there is “potential therapeutic benefit for the subject and no more than minimal risk for adverse events” (Peterson and Wallin, 2003). The proportion in favor of proxy consent however drops substantially if there is “no potential therapeutic benefit for the subject with no more than minimal risk for adverse events but potential therapeutic benefit to others”.…”
Section: Discussionmentioning
confidence: 99%
“…A debated issue in dementia research concerns obtaining informed consent from patients with impaired cognitive function (e.g. Peterson and Wallin, 2003;Slaughter, Cole, Jennings, & Reimer, 2007). Critical ethical issues associated with medical decision-making concern for example patient autonomy.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…An inquiry in Sweden demonstrated that women and laypersons were generally keener to preserve a patient's integrity and medical professionals were more willing than laypersons to permit individuals with dementia to participate in placebo-controlled trials (Peterson &Wallin 2003). Confidentiality in research is critically important, but it is not an absolute legal principle in either research or clinical settings (Stiles & Petrila, 2011).…”
Section: Attitudes Towards Inclusion Of Older People In Research Protmentioning
confidence: 99%